2021
DOI: 10.1108/ijshe-10-2020-0368
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level characteristics of environmental sustainability among students in a higher education institution: the role of happiness and academic performance

Abstract: Purpose Students play an unequivocal role in sustainable universities as they are theorized to embody the mission of a sustainable university through a sustainable lifestyle and spread sustainability practices during their professional careers. Despite this, it is not well known how or why students come to embody a sustainable lifestyle. This study aims to better understand the relationship between happiness, academic achievement and sustainability behaviors among the student population in a Mexican higher edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Although great experimental evidence has demonstrated strong restorative outcomes associated with natural scenes and settings, there are limited studies that have evaluated the relation between built environments and psychological status among university students [5]. The available research focused mainly on the influences of socio-demographic factors, social networks, and interpersonal problems that could be attributed to psychological distress [6,7]. Thus, it is worthwhile to examine the role of restorative environments (in this case, an on-campus ecological wetland) in mediating psychological distress among university students.…”
Section: Introductionmentioning
confidence: 99%
“…Although great experimental evidence has demonstrated strong restorative outcomes associated with natural scenes and settings, there are limited studies that have evaluated the relation between built environments and psychological status among university students [5]. The available research focused mainly on the influences of socio-demographic factors, social networks, and interpersonal problems that could be attributed to psychological distress [6,7]. Thus, it is worthwhile to examine the role of restorative environments (in this case, an on-campus ecological wetland) in mediating psychological distress among university students.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between psychological happiness and motivational academic life achievements on sustainability deserves to be more deeply explored (Giannetti et al , 2021b). Happy people can be healthier and more productive (Oswald et al , 2015; Ma et al , 2022).…”
Section: Theoretical Background Of the Used Methods To Quantify Stude...mentioning
confidence: 99%
“…The literature on Sustainable University concepts mainly focuses on three different approaches: the institution's infrastructure (Almeida et al , 2013; Oliveira et al , 2018), the didactic–pedagogical system and the design of a sustainable curriculum (Lukman and Glavič, 2007; Van Weenen, 2000) focused on the students (Alves-Pinto and Giannetti, 2019; Giannetti et al , 2021b). Regarding universities’ infrastructure, several studies are focusing on their management operation systems, aiming to reduce the environmental impact of the university campus (Jain et al , 2017; Savely et al , 2007) by implementing a more sustainable physical structure (Jose and Chacko, 2017; Aisheh et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study reported that students felt happier after participating in an energy initiative on campus (Escobar-Tello and Bhamra 2013). More recently, in a study among Mexican higher education students, the happiest and most academically bright were found to be slightly environmentally sustainable, though more empirical is needed to validate its value (Alves-Pinto and Giannetti 2019; Giannetti et al 2021).…”
Section: Happiness and More Sustainable Universities: A Future Questmentioning
confidence: 99%